Pengetahuan Kanak-Kanak Sekolah Rendah mengenai Penganiayaan Seksual (Jurnal Pembangunan Sosial, 2013)
The purpose of this study was to assess primary school children’s knowledge of sexual abuse. This research sought to identify the children’s level of knowledge regarding sexual abuse, and to examine whether there were differences in their levels of knowledge based upon year of study and gender. Two hundred and thirty-nine participants from Year Two, Year Four, and Year Six classes were recruited from a primary school in the northern region of Malaysia. The Children’s Knowledge of Abuse (CKAQ) – Revision III was utilized as 84 Jurnal Pembangunan Sosial Jilid 16 the research instrument. The results indicate that levels of knowledge were not affected by year of study or gender. However, knowledge did differ based upon year of study when analysis was conducted on the Inappropriate Touch subscale, where Year Four students were found to have poorer knowledge of abuse than their Year Six counterparts. Signifcant results were also obtained for gender in the Appropriate Touch subscale. Girls were found to score less than boys in this subscale.